Current Methods to Investigate Nociception and Pain in Zebrafish - Ohnesorge, Nils; Heinl, Céline; Lewejohann, Lars (Frontiers in Neuroscience, 2021)
Pain is an unpleasant, negative emotion and its debilitating effects are complex to manage. Mammalian models have long dominated research on nociception and pain, but there is increasing evidence for comparable processes in fish. The need to improve existing pain models for drug research and the obligation for 3R refinement of fish procedures facilitated the development of numerous new assays of nociception and pain in fish. The zebrafish is already a well-established animal model in many other research areas like toxicity testing, as model for diseases or regeneration and has great potential in pain research, too. Methods of electrophysiology, molecular biology, analysis of reflexive or non-reflexive behavior and fluorescent imaging are routinely applied but it is the combination of these tools what makes the zebrafish model so powerful. Simultaneously, observing complex behavior in free-swimming larvae, as well as their neuronal activity at the cellular level, opens new avenues for pain research. This review aims to supply a toolbox for researchers by summarizing current methods to study nociception and pain in zebrafish. We identify treatments with the best algogenic potential, be it chemical, thermal or electric stimuli and discuss options of analgesia to counter effects of nociception and pain by opioids, nonsteroidal anti-inflammatory drugs (NSAIDs) or local anesthetics. In addition, we critically evaluate these practices, identify gaps of knowledge and outline potential future developments.